Soundtracks of Empire: “The White Man’s Burden,” the War in the Philippines, the“Ideals of America,” and Tin Pan Alley - Robert W. Rydell (European Journal of American Studies)
America’s War with Spain inspired Tin Pan Alley music publishers to generate popular songs to accompany America’s military victories and subsequent occupation of Cuba, Puerto Rico, Hawaii, and the Philippines. By expanding the genre of the so-called “coon song” to include the people of these islands, composers and publishers contributed to the domestication of empire in fin-de-siècle America.